The eating attitudes of the university students, self-efficacy and affecting factors - ERGÜN, AYŞE (MARMARA UNIV, INST HEALTH SCIENCES, 2015)
Objective: This research was performed to figure out eating attitudes of students, self-efficacy and factors that influence it. Method: This descriptive research was conducted with 525 university students. The data were collected with an identifier form, eating attitude test (EAT-40) and self-efficacy scale. In order to evaluate data, descriptive statistics, chi-square analysis, Mann-Whitney U test, Spearman correlation analysis and logistic regression analysis were used. Results: The mean score of the EAT-40 was 17.91 +/- 11.10. There was a statistically significant difference (z=-2.39, p=0.01) between the mean EAT-40 score of female students (18.67 +/- 11.30) and male students (16.79 +/- 10.73). The rate of students with EAT-40 score over 30 were found as 7.1% in the 18-19 age group, 10.9% in the 20-21 age group and 17.6%in the 22-24 age group (x(2) = 7.732; p<0.05). The eating disorder risk of the over weight and obese students was two times more than the students with normal weight, while the eating disorder risk of the weak students was 2.9 times lower than the students with normal weight. There was no difference between the mean self-efficacy score of the ones whose EAT40 score was over 30 and under 30. Conclusions: The students being overweight and obese, being not happy about their weights, being on a diet and stating that their nutrition would be affected in case of stress were found at risk in terms of the eating disorder.
Keywords: Eating disorders; self-efficacy; eating attitude; EAT-40; university students; BODY-IMAGE; BEHAVIORS; METAANALYSIS; ADOLESCENTS; DISORDERS; GIRLS; RISK